Deformable Objects with Real Time Realistic Behaviour for Virtual Scenarios - Dias, J.; Rebordão, J. M.; Gallo, R.; Palmer, P. (The Internet in 3D : Information, images and interaction, 1997)
A network connection can provide a window to the world of information, where data and programs can be exchanged with many other users. Styles of virtual and multimedia information are now being developed that will become an integral part of these interactions. This volume covers this area, discussing techniques and applications of using 3-D and multimedia on the Internet.